ANALISIS YURIDIS PENJATUHAN PIDANA PADA TINDAK PIDANA PENCABULAN DENGAN KEKERASAN (Studi Putusan Nomor 680/Pid.B/2016/PN. Mlg) - Edisama Buulolo (Jurnal Panah Hukum, 2022)
Criminal acts that have not been completed are not always unpunished. However, it is necessary to know what is the reason why the criminal act was not completed. In Article 53 paragraph (1) of the Criminal Code it is explained that an attempt to commit a crime can be punished if the crime is not completed due to obstacles, not the will of the perpetrator of the crime itself. This study aims to determine and analyze the criminal imposition of criminal acts of obscenity with violence. The type of research used is normative law research with data collection techniques carried out by literature study (secondary data). The data analysis used in this research uses qualitative data analysis systematically and is described in a descriptive form. The results obtained are studied deductively and then a conclusion is drawn which is a manifestation of the problem under study or the subject matter under discussion. Based on research findings and discussion of the Malang District Court decision No. 680/Pid.B/2016/PN. Mlg, the authors conclude that the criminal act committed by the defendant is a criminal act of obscenity with violence. Criminal imposition on the crime of obscenity with violence is in accordance with the legal provisions in Article 289 of the Criminal Code. The criminal act committed by the defendant was not an attempt to commit a crime because the criminal act committed by the defendant was not completed due to other elements not because of the will/intention of the defendant. As for the author's suggestion, namely that the demands of the public prosecutor are very low, the demands of the public prosecutor should be a minimum of 4.5 years in prison and the judge as a justice breaker should not only be based on the demands of the public prosecutor. Judges should be able to provide legal justice especially to children and women